2014
DOI: 10.14341/dm2014425-34
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with in-hospital mortality after coronary artery bypass grafting in patients with CHD and type 2 diabetes

Abstract: Coronary artery bypass grafting (CABG) is the main method used for myocardial revascularisation in patients with diabetes mellitus (DM), and determining the factors affecting the outcomes of CABG in these patients is important. Objective. To identify risk factors for in-hospital mortality after coronary artery surgery (CABG) for patients with and without type 2 diabetes mellitus (T2DM). Methods. A retrospective analysis of the medical records of patients who underwent CABG from 2006 to 2009 was conducted. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
1
0
7
Order By: Relevance
“…Despite the fact that in-hospital mortality rates among diabetic patients significantly decreased from 3% in the period 1998-2002 to 1.3% in the period 2003-2005 [35], postoperative complication rates remain high. Thus, a retrospective analysis, comprising 667 CAD patients, who have undergone CABG, showed that diabetes did not affect in-hospital mortality, but was an independent predictor of sternal wound infection [41]. Similar findings were obtained in another retrospective study, suggesting the absence of any correlations between diabetes and the risk of cardiovascular complications and mortality.…”
Section: Diabetes Mellitus and Outcomes Of Myocardial Revascularizationsupporting
confidence: 73%
“…Despite the fact that in-hospital mortality rates among diabetic patients significantly decreased from 3% in the period 1998-2002 to 1.3% in the period 2003-2005 [35], postoperative complication rates remain high. Thus, a retrospective analysis, comprising 667 CAD patients, who have undergone CABG, showed that diabetes did not affect in-hospital mortality, but was an independent predictor of sternal wound infection [41]. Similar findings were obtained in another retrospective study, suggesting the absence of any correlations between diabetes and the risk of cardiovascular complications and mortality.…”
Section: Diabetes Mellitus and Outcomes Of Myocardial Revascularizationsupporting
confidence: 73%
“…Критериями исключе-ния являлись: неконтролируемая артериальная гипертензия, АВ-блокада II-III степени, наличие гемодинамически значимых стенозов клапанов с недостаточностью III-IV степени, декомпенси-рованная ХСН и нарушения углеводного обмена за исключением СД 2 типа (нарушение гликемии натощак, нарушение толерантности к углеводам, СД 1 типа). Диагноз СД 2 типа устанавливали в соответствии с действующими национальными рекомендациями [15]. В 1-ю группу (n=23) вошли пациенты с ИБС и со сниженной сократительной способностью миокарда, а во 2-ю группу -30 больных с ИБС, ассоциированной с СД 2 типа и низкой ФВ ЛЖ.…”
Section: материалы и методыunclassified
“…В то же время во многих недавних исследованиях такой взаимосвязи проследить не удалось [33][34][35][36]. Возможно, причиной этого является тот факт, что в последние годы отмечено улучшение понимания патофизиологии диабета, а также до-и интраоперационного ведения этой категории боль-ных.…”
Section: сахарный диабет Diabetes Mellitus 474unclassified
“…[37]. В исследованиях, проведен-ных на когорте пациентов, подвергшихся КШ в 2006-2009 гг., уровень госпитальной смертности в группе СД составил 1,6%, в группе без диабета -2,0% (р=0,682) [34].…”
Section: сахарный диабет Diabetes Mellitus 474unclassified
See 1 more Smart Citation